Pengaruh Perencanaan Anggaran, Pencatatan Administrasi, Sumberdaya Manusia, Komitmen Organisasi dan Lingkungan Birokrasi terhadap Penyerapan Anggaran PNBP Kegiatan Pengamanan Objek Vital pada Satker Jajaran Polda Riau - Yanuriza, Yanuriza; Hasan, Amir; Rasuli, Muhammad (Jurnal Ekonomi, 2019)
This study aims to look at the factors that affect the budget absorption of vital object security activities in Riau Regional Police Work Unit. The sampling method uses pruposive sampling and sample transmission using an error rate of 5%. The author conducts research based on data collection techniques through questionnaires. The analysis of the data that I use is the quantification of data through multiple linear regression analysis with t test, R2 and collecting data processed with the help of the SPSS 22.0 statistical program. From the results of the study conclusions were obtained as partial that five variables t (2,392; 3,109; 2,971; 2.038; and 1,106). With the results of the variables namely budget planning, administration records, human resources, organizational commitment influences budget absorption while the bureaucratic environment variable does not affect the absorption of the budget in the safeguard activities of vital objects in the Riau Police Regional Working Unit. In addition, it can be seen from the determination of the test where the R value of 0.819 and adjusted R2 of 0.624 or 62.4% of the independent variables affect the dependent variable and 37.6% is influenced by other variables